Miocene block uplift and basin formation in the Patagonian foreland: The Gastre Basin, Argentina - Bilmes, Andrés (2013)
The intraplate fault-block mountains and intermontane deposits of the Gastre Basin, which are recorded more than 550 km east of the Andean trench in central Patagonia, Argentina, are analysed. The Gastre Basin is one of the largest Patagonian intermontane basins, limited by uplifted blocks strongly oblique to the Andean chain. It was originated by reverse faulting and inversion of pre-existing normal faults associated with a Mesozoic rift basin and defined by older crustal heterogeneities. The deformational event occurred during the middle Miocene, related to a short contractional episode (16.1?14.86 Ma), probably in response to an eastward migration of the Andean fold and thrust belt. During Pliocene to Quaternary times, neither younger fault-block uplifts nor reconfigurations of the basin occurred. Similarities between the study area and other parts of the Patagonian foreland?such as the presence of Miocene reverse or inversion tectonics, as well as the accommodation of the Miocene sedimentary successions?suggest that the Gastre Basin is part of a major late early to middle Miocene broken foreland system (i.e. the Patagonian broken foreland) that exhumed discrete fault-block mountains and generated contemporary basins along more than 950 km parallel to the Andean trench (i.e. between 40°00′ and 48°00′ south latitude). Based on recent studies on the southern Andean Margin, this continental-scale contractional episode may be the result of a flat-slab subduction segment. Nevertheless, such a hypothesis is very difficult to support when analysing such a large flat subduction segment along the entire Patagonian trench. This suggests the need to consider alternative flat-slab trigger mechanisms or other factors in the generation of broken foreland systems.